A randomized controlled clinical trial on the impact of CCR5 blockade with maraviroc in early infection on T-cell dynamics. Issue 44 (November 2016) - Karris, Maile Y.; Umlauf, Anya; Vaida, Florin; Richman, Douglas; Little, Susan; Smith, Davey
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Initiation of antiretroviral therapy (ART) in early HIV infection demonstrates clinical benefits including enhanced CD4 + T-lymphocyte recovery and minimization of the latent HIV reservoir. Whether ART intensification with CCR5 blockade provides additional benefits is unknown. Trial design: : This randomized controlled trial evaluated the impact of maraviroc (MVC) intensification in persons starting ART in acute and early HIV (AEH, within 3 months of estimated date of infection). Methods: Twenty persons in AEH in San Diego underwent double-blind randomization to receive either standard of care (SOC) ART or SOC + MVC to evaluate the hypothesis that early CCR5 blockage with a CCR5-containing ART regimen may provide immunologic and clinical benefit. The primary outcome of this study was the difference from baseline to week 48 in the proportion of CCR5 + CD4 + memory T cells. Blood was drawn at baseline and weeks 12, 24, and 48 to evaluate CCR5 + CD4 + and CD8 + T-cell dynamics using multicolor flow cytometry. Results: MVC intensification (n = 10) did not significantly alter CCR5 + T-cell dynamics at week 48 of study compared to SOC (n = 9) in this fully recruited study (mean 1.12 vs 0.63, t = 0.36, df = 16, P  = 0.727). Exploratory analyses of additional T-cell subsets suggest that MVC intensification in AEH trended to early greater increases in naïve and activated and proliferating CD4 + T cells ( P  = 0.11, 0.19), and greater decreases in senescent memory CD4 + T cells ( P  = 0.06), but these differences did not remain by week 48. CD8 + T-cell evaluations did demonstrate trends to differences at week 48 with slower increases in naïve cells and slower decreases in activated memory cells ( P  = 0.16, 0.09). There were no reported harms or significantly different adverse events. Conclusions: We did observe a few trends, but did not find compelling evidence that MVC intensification during AEH significantly impacts CD4 + and CD8 + T-cell dynamics. Diagnosing and starting persons in AEH on ART may be of greater clinical importance than the regimen initiated.